1988
DOI: 10.1093/infdis/158.6.1227
|View full text |Cite
|
Sign up to set email alerts
|

Chronic-Dose Acyclovir to Suppress Frequently Recurring Genital Herpes Simplex Virus Infection: Effect on Antibody Response to Herpes Simplex Virus Type 2 Proteins

Abstract: To determine the effect of prolonged suppressive acyclovir therapy on the antibody response to herpes simplex virus type 2 (HSV-2) proteins, we studied sequential sera from 33 patients with frequently recurring (six or more recurrences per year) genital herpes. Twenty-two patients received 400 mg of oral acyclovir and 11 received placebo, twice daily for one year. Sera collected at enrollment, after six months and 12 months of therapy, and during the first recurrence after cessation of therapy were evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…This is consistent with clinical results in patients undergoing acyclovir treatment, as reported by Lafferty et al (1984) and Mitchell et al (1986). Clinical observations concerning the immune response of HSV-infected patients showed a lower antibody titre in acyclovir-treated patients than in placebo-treated patients, resulting in suppression of antibody response or lymphoproliferative responses to HSV (Ashley & Corey, 1984;Bernstein et al, 1984;Lafferty et al, 1984;Mitchell et al, 1986;Erlich et al, 1988;Gold et al, 1988;Ragab et al, 1989;Kawana et al, 1995;Hu et al, 1997). Results of the present study would be applicable in interpreting those observations, although it is difficult to deny the possibility that antibody titre is dependent on the severity of skin lesions.…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with clinical results in patients undergoing acyclovir treatment, as reported by Lafferty et al (1984) and Mitchell et al (1986). Clinical observations concerning the immune response of HSV-infected patients showed a lower antibody titre in acyclovir-treated patients than in placebo-treated patients, resulting in suppression of antibody response or lymphoproliferative responses to HSV (Ashley & Corey, 1984;Bernstein et al, 1984;Lafferty et al, 1984;Mitchell et al, 1986;Erlich et al, 1988;Gold et al, 1988;Ragab et al, 1989;Kawana et al, 1995;Hu et al, 1997). Results of the present study would be applicable in interpreting those observations, although it is difficult to deny the possibility that antibody titre is dependent on the severity of skin lesions.…”
Section: Discussionsupporting
confidence: 86%
“…Alternatively, this diminished response could be due to an immunosuppressive effect of the drug. In this regard, Gold et al (4) reported that long-term administration of ACV did not affect levels of antibodies to cytomegalovirus and rubella virus, while it reduced levels of antibody to HSV-2-related proteins. Bernstein et al (2) also noted that an immunosuppressive effect of ACV seemed unlikely, since the drug level necessary to cause such an effect would be much greater than that detected in ACV-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Acyclovir is commonly used to treat infection with another member of the herpesvirus family, herpes simplex virus (HSV). The effect of acyclovir therapy on the humoral immune response to HSV proteins has been analyzed by sensitive techniques such as Western blot (immunoblot) analysis and radioimmunoprecipitation (3,6,13). Furthermore, functional analogies and structural homologies have been drawn between certain gene products of HSV and VZV.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term oral acyclovir for the treatment of primary genital herpes in the immunocompetent host has been related to a decrease in the humoral response to specific polypeptides of HSV, including HSV gE (3,6). Acyclovir therapy also appears to delay the development of antibody to a number of different HSV-specific polypeptides, including those corresponding to glycoproteins D and E of HSV, and prolonged (6-to 12-month) daily suppression of genital herpes has been shown to decrease levels of antibodies to many major immunogens of HSV-2 (13). Aithough acyclovir therapy appears to influence the frequency and the magnitude of antibody response to different HSVspecific polypeptides, a similar effect was not present in the antibody response to VZV-specific polypeptides in children who received a short oral course of acyclovir.…”
Section: Discussionmentioning
confidence: 99%